The Influence Of Product Quality, Service Quality, and Promotion On The Decision To Saving of Bank Syariah Indonesia Customers In Malang City - Nadia Intan Carolina; Khusnudin (Program Studi Ekonomi Syariah, Fakultas Agama Islam Universitas Islam Riau, 2024)
The purpose of this study was to examine and analyze the effect of product quality, service quality and promotion on the saving decisions of Bank Syariah Indonesia customers in Malang City. The research approach used is quantitative research. The sampling technique in this study used the Non Probability Sampling technique with a purposive sampling method. The sample required is 85 respondents with the criteria of Bank Syariah Indonesia customers who have savings and savings accounts for the period January 27 2021 until now and are domiciled in Malang City. The data used in this study are primary data and secondary data. Data processing and analysis in this study used an analytical tool in the form of the SPSS version 24 application which aims to calculate statistical values in the form of data quality testing, classical assumption testing, hypothesis testing, and multiple linear regression analysis. The results of this study indicate that product quality (X1) partially has a significant effect on saving decisions (Y), service quality (X2) partially has no significant effect on saving decisions (Y), Promotion (X3) partially has a significant effect on saving decisions. (Y), and product quality (X1), service quality (X2) and promotion (X3) simultaneously have a significant effect on saving decisions (Y).